An Unexpected FeCl3/C-Catalyzed β-Stereoselective Glycosylation in the Presence of the C(2)-Benzyl Group - Guo, Hong; Si, Wenshuai; Li, Juan; Yang, Guofang; Tang, Tianjun; Wang, Zhongfu; Tang, Jie; Zhang, Jianbo (Synthesis, 2019)
An efficient and completely β-stereoselective glycosylation that did not rely on neighboring group participation is described using 2–20 mol% FeCl3/C as the catalyst and benzylated propargyl glycosides as the donors to reach yields up to 96% under mild condition. With an octatomic-ring intermediate at the α-face of FeCl3/C with alkyne of propargyl glycosides, a panel of aglycones comprising aliphatic, alicyclic, unsaturated alcohols, halogenated alcohols, and phenols with different substitution were examined successfully for the exclusive β-stereoselective glycosylation reaction.
Keywords: propargyl glycosides; glycosylation; β-stereoselective; C(2)-benzyl group; FeCl3/C